INTERMEDIATE LEVEL SEWING SKILLS TRAINING IN INCREASING INDEPENDENCE FOR MATANGKULI ASSISTED VILLAGERS - Falahuddin; Erna Isfayani; Wulandari; Fuadi; Reza Juanda; Ramadhan Razali; Rico Nur Ilham (RADJA PUBLIKA, 2024)
Sewing training was held as a contribution to improving the competence of individuals and community groups, especially mothers at UKM Bungong Jaroe, Sumbok Rayeuk village, Nibong sub-district, North Aceh district. The aim of this service activity is not only to provide additional special knowledge for mothers who have free time, to provide the opportunity to be independent with a home business but do not yet have the skills, as well as to build relationships with local residents. By carrying out this service, it is hoped that the participants will be able to carry out sewing businesses independently and in groups so that they can contribute to meeting family needs. This series of assistance also includes assistance in business management administration, additional production facilities; repair of business premises, sewing and embroidery machine support as well as intermediate level sewing training. The training participants consisted of group members who were already able to sew and 20 novice tailors. Involving certified instructors from training institutions in their fields. This activity is supported by PT PEMA Global Energi (PGE) and the Cendikia Community Ukhuwah Foundation (YUMC).